2010
DOI: 10.1208/s12249-010-9435-7
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Optimization of Zinc-Pectinate Beads for the Controlled Delivery of Resveratrol

Abstract: Preventive and therapeutic efficacies of resveratrol on several lower gastrointestinal (GI) diseases (e.g., colorectal cancer, colitis) are well documented. To overcome the problems due to its rapid absorption and metabolism at the upper GI tract, a delayed release formulation of resveratrol was designed to treat these lower GI diseases. The current study aimed to develop a delayed release formulation of resveratrol as multiparticulate pectinate beads by varying different formulation parameters. Zinc-pectinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 38 publications
5
27
0
2
Order By: Relevance
“…. (7) hour the swelling percentage in pH 6.8 and 7.4 medium decreases [11,28]. The result shows that the distribution of pH 5.0 SI data that is analyzed is distributed normally.…”
Section: Hesperidin Hydrogel Swelling Indexmentioning
confidence: 80%
See 2 more Smart Citations
“…. (7) hour the swelling percentage in pH 6.8 and 7.4 medium decreases [11,28]. The result shows that the distribution of pH 5.0 SI data that is analyzed is distributed normally.…”
Section: Hesperidin Hydrogel Swelling Indexmentioning
confidence: 80%
“…Pectin, with its characteristic as a weak acid (pKa 3-4) with the carboxylic group (-COO-) tends to ionize at higher pH. This causes a repelling force among the carboxylate group in pectin leading to the increase of hydrogel swelling power [11]. The highest swelling percentage was achieved in pH 6.8 medium after 5 h, at the 6 ) in chitosan will occur, while pectin is unionized, so repelling force takes place inside the chitosan structure which causes significant swelling in formula with higher chitosan concentration (formula 2 and 4) [2].…”
Section: Hesperidin Hydrogel Swelling Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…With the great number of hydrogen bonds, the ability to bind with water and the ability to swell in water become greater [9]. When compared with the research from Das et al, the swelling ability of Surini and Diandra Int J App Pharm, Vol 9, Suppl 1, 2017, hydrogel beads is <100%, whereas the swelling ability of mulberry leaf extract was better, at more than 200% [8].…”
Section: Swelling Abilitymentioning
confidence: 99%
“…Zinc is a cation divalent that is cross linked with the carboxyl group of pectin to create hydrogel beads. A study reported that zinc possesses a high ability to bind with pectin, which can form beads with a greater gel strength [8]. This research aims to make and evaluate mulberry leaf extract hydrogel beads with pectin as a polymer and zinc acetate as a cross linker to produce a nutraceutical product in a bead dosage form.…”
Section: Introductionmentioning
confidence: 99%